Barbados. Significant achievements 2016 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The main activities carried out by the Institute in Barbados during 2016 are identified, with respect to the needs and interests of the country, strengthening issues such as innovation, beekeeping, agrotourism, governance, plant health, animal health, resilience against climate change, health and food safety. Finally, it supported the improvement of the occupational standard and the value chains of rum and coconut.